Equity research - Airbnb, Inc - Teixeira, Tiago Pinho Osório Araújo (2022)
This report describes aims to give a price target for one of the world ́s largest companies in the Travel & Tourism industry which lodges over 150 million users every year in over 200 countries. Is important to highlight that this industry was one of the most impacted by the COVID-19 pandemic. Nonetheless, Airbnb is well positioned to capitalize from T&T recovery. But, fundamentals and current market conditions don’t fully justify Airbnb`s current valuation, which we explain in detail in this report.